Energy geo-structures: A review of their integration with other sources and its limitations - Aresti, Lazaros; Alvi, Maria Romana; Cecinato, Francesco; Fan, Tao; Halaj, Elzbieta; Li, Zili; Okhay, Olena; Poulsen, Soren Erbs; Quiroga, Sonia; Suarez, Cristina; Tang, Anh Minh; Valancius, Rokas; et al. (My University, 2024)
Ground Source Heat Pumps, in the framework of Shallow Geothermal Energy Systems, outperform conventional Heating Ventilation and Air Conditioning systems, even the high efficiency Air Source Heat Pumps. At the same time, though, they require considerably higher installation costs. The utilization of dwellings' foundations as ground heat exchanger components has recently demonstrated the potential to generate significant cost reductions primarily attributed to the reduction in expenses associated with drilling and backfill material (grout). These elements are referred to in the literature as Thermo-Active Structures or Energy Geo-structures (EGs). The current study employs a ‘mixed studies’ review (i.e., literature review, critical review and state-of-the-art review) methodology to comprehensively examine and assess the compatibility and integration of different renewable energy sources and environmentally friendly technologies with foundation elements deployed as EGs. These mainly include heat pumps, district heating and cooling networks, solar-thermal systems, waste heat, biomass and other types such as urban structures. Emphasis has been given on the advancement on this area, with the current study identifying and addressing two primary categories. The first category involves the integration of EG elements with sources that are able to supply green electricity, referring to renewable energy electricity obtained from on-grid or off-grid integration. The second category, involves a direct or indirect integration with sources that provide heat, or vice versa. The technical and non-technical barriers of such integrations have been discussed in detail, with the technical challenges generally involving engineering design, and system optimization, whereas non-technical challenges encompassing the economic, social, and policy domains.
Keywords: Energy geo-structures barriers; Geothermal energy integration; Shallow geothermal energy; Energy geo-structures; Geothermal energy potential